Estimation of the relative biological effectiveness of heavy ions using the dose-mean transfer energy (2019)
Ionizing radiations induce damages in DNA when interacting with living beings. These damages may lead to biological effects such as chromosome aberrations and cell death. The radiation potential for inducing DNA damages is related to the capacity of radiation to produce densely ionization patterns in the irradiated tissues. This capacity is often related to the linear energy transfer (LET); however, this quantity is not enough for determining the relative biological effectiveness (RBE) of a given radiation quality. For instance, two heavy charged particles (ions) with the same LET show different RBE. So far, researchers have used the dose-mean lineal energy as a quantity to estimate the RBE of ionizing radiations. In this work, we explore a new microdosimetric quantity called dose-mean energy transfer. We also implemented a computational tool for the calculation of such variables using Geant4-DNA toolkit. In addition, a comparison with another classical microdosimetric variable known as dose-mean linear energy was made and RBE variable was determined for each of them. The results show consistent values between dose-mean linear energy and the proposed new microdosimetric variable dose-mean transfer energy. Finally, based on the results obtained for the RBE of each of the variables, the impact of the new variable on the RBE estimation was studied.